Análisis de la Reincidencia y abuso del régimen semiabierto por acumulación de penas en el Ecuador - Alvear Estévez, Paola Alexandra (2024)
Criminal recidivism and abuse of the semi-open regime by accumulation of sentences are complex and worrisome problems within the Ecuadorian penitentiary system. Despite efforts to rehabilitate and reintegrate persons deprived of liberty (PPL) into society, the persistence of new crimes highlights the shortcomings of rehabilitation programs and prison management policies. Article 201 of the Constitution of the Republic of Ecuador (CRE) establishes that the purpose of punishment is the reintegration of the individual into society, which is a fundamental premise for the construction of a justice system that prioritizes human rights and the dignity of individuals. However, the accumulation of sentences and the consequent abuse of the semi- open regime represent a significant challenge in this process. Therefore, for this research, the general objective was set as follows: To evaluate the efficiency of the semi-open regime in relation to the criminal recidivism of PPL, considering that the methodology applied was a descriptive, documentary research, through the application of deductive, analytical, synthetic method with a mixed approach, where an interview guide was used to five criminal judges in order to obtain information on the semi-open regime and criminal recidivism, in the same way a structured base survey was used to legal professionals with the purpose of having relevant data on the research topic. In this context, a database of 91 PPL of the Sucumbíos Deprivation of Liberty Center, who are part of the semi-open regime, was analyzed on recidivism, identifying that in the first four months of the year 2023 they have not reoffended, which is considered a positive factor for this research.